Excavating Embodied Literacies Through a Chicana/Latina Feminist Framework. (March 2021) - González Ybarra, Mónica; Saavedra, Cinthya M.
In this article, the authors take a reflective, self-study journey that digs into their own embodied literacies as Chicana feminist literacy researchers. Chicana/Latina feminisms offer an/other angle for exploring embodied literacies and are one way to center bodies and knowledge from the margins. The authors emphasize Anzaldúa's concept of geographies of selves as an entry point for theorizing the embodied literacies of Chicanas/Latinas. To support this excavation process, the authors demonstrate how autohistoria-teoría, as a methodological approach to literacies, can be used to locate, narrate, and document the embodied literacies of Chicanas/Latinas. The findings demonstrate how places and people shape knowledge and ways of reading the world and thus impact the literacies imprinted on bodies.